2021
DOI: 10.33365/ji-mr.v2i1.1065
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kecerdasan Numerik Dan Minat Belajar Terhadap Kemampuan Penalaran Matematis Siswa SMP

Abstract: The purpose of this study was to determine the effect of numerical intelligence on students' mathematical reasoning abilities, to determine the effect of interest in learning on students' mathematical reasoning abilities, to determine the influence of numerical intelligence and interest in learning on students' mathematical reasoning abilities. The method used in this study is quantitative with a correlation approach. The sample in this study were students of SMPN 13 Pesawaran class VIII who were randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
3
0
11
Order By: Relevance
“…Kemudian siswa diberikan angket motivasi belajar melalui link google form sebanyak 30 butir pernyataan yang terdiri dari 18 pernyataan positif dan 12 pernyataan negatif yang sudah tervalidasi. (Hikmah & Saputra, 2023) yaitu adanya dorongan dan kebutuhan untuk belajar, adanya harapan dan cita-cita masa depan, adanya penghargaan dalam belajar, adanya kegiatan yang menarik dalam belajar dan adanya lingkunga belajar yang kondusif. Angket diadopsi dari (Novianti et al, 2020) yang sudah divalidasi.…”
Section: Metodeunclassified
“…Kemudian siswa diberikan angket motivasi belajar melalui link google form sebanyak 30 butir pernyataan yang terdiri dari 18 pernyataan positif dan 12 pernyataan negatif yang sudah tervalidasi. (Hikmah & Saputra, 2023) yaitu adanya dorongan dan kebutuhan untuk belajar, adanya harapan dan cita-cita masa depan, adanya penghargaan dalam belajar, adanya kegiatan yang menarik dalam belajar dan adanya lingkunga belajar yang kondusif. Angket diadopsi dari (Novianti et al, 2020) yang sudah divalidasi.…”
Section: Metodeunclassified
“…More specifically, the achievement of mathematics learning objectives can be seen in the following research results, which state that students' mathematical understanding abilities are in a low category (Nurdiyana et.al., 2022), students do not have good reasoning abilities (Agusti, 2023), students' mathematical problem-solving abilities are at low qualifications (Krisnawati & Iyam, 2020), students' mathematical communication abilities are still relatively low (Zaditania & Ruli, 2022), and students' mathematical connection abilities are low (Widiyawati et.al, 2020). Furthermore, from the affective aspect, it was found that there are still many students whose learning motivation is low (Hikmah & Saputra, 2022), and the level of students' self-confidence in learning mathematics is also still relatively low (Pangestu & Sutirna, 2021). These results show that mathematics learning objectives have not yet been achieved optimally (Ariati & Juandi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Students with high curiosity about the various problems available, will probably develop high learning enthusiasm and are able to connect what will be learned as a goal, orientation, and are more confident when conveying ideas (Astuti & Hikmah, 2021). Interest in learning is a comprehensive implication of students with an effort to pour all their ideas and interests to gain knowledge and reach an understanding of the knowledge sought (Hikmah, 2021). Therefore, interest and conceptual understanding in learning mathematics will affect students' mathematics learning achievement regarding the materials and subsequent materials.…”
Section: Introductionmentioning
confidence: 99%